2011
DOI: 10.1158/1078-0432.ccr-10-2443
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of T-cell–Mediated Antitumor Response: Angiostatic Adjuvant to Immunotherapy against Cancer

Abstract: Purpose Tumor-released pro-angiogenic factors suppress endothelial adhesion molecule (EAM) expression and prevent leukocyte extravasation into the tumor. This is one reason why immunotherapy has met with limited success in the clinic. We hypothesized that overcoming EAM suppression with angiogenesis inhibitors would increase leukocyte extravasation and subsequently enhance the effectiveness of cellular immunotherapy. Experimental Design Intravital microscopy, multiple-color flow cytometry, immunohistochemist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 38 publications
3
52
0
Order By: Relevance
“…This antitumor effect was attributed to dramatic infiltration of DC-activated iNKT cells and subsequent induction of apoptosis in the tumor cells. It was recently reported that inhibition of angiogenesis lead to normalized endothelial adhesion molecule levels and improves tumor growth inhibition by promoting leukocyte extravasation (Dings et al, 2011). Upregulation of VCAM1 expression was also induced in the endothelium of apelin-expressing tumor, and it would promote iNKT cell infiltration.…”
Section: Apelin Improves Immunotherapy By Vessel Maturationmentioning
confidence: 96%
“…This antitumor effect was attributed to dramatic infiltration of DC-activated iNKT cells and subsequent induction of apoptosis in the tumor cells. It was recently reported that inhibition of angiogenesis lead to normalized endothelial adhesion molecule levels and improves tumor growth inhibition by promoting leukocyte extravasation (Dings et al, 2011). Upregulation of VCAM1 expression was also induced in the endothelium of apelin-expressing tumor, and it would promote iNKT cell infiltration.…”
Section: Apelin Improves Immunotherapy By Vessel Maturationmentioning
confidence: 96%
“…Accordingly, we included 5 linear (9-13) peptides and 20 different side-chain cyclized peptides (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) covering this region ( Fig. 1D and SI Appendix, Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Angiogenic growth factors contribute to immune suppression by down-regulation of endothelial adhesion molecules (12)(13)(14), inhibition of dendritic cell maturation (15), and attraction and proliferation of immunosuppressive cells (16,17). Conversely, antiangiogenic drugs can help reverse the immunosuppressive state in cancer patients (14,18,19). Therefore, an angiostatic vaccination approach against VEGF can potentially inhibit tumor growth via multiple mechanisms (20).…”
mentioning
confidence: 99%
“…Calix [4]arene 0118 (Scheme 4) is a proven potent antiangiogenic agent that effectively inhibits tumor growth in preclinical studies and is presently under investigation in a phase-I clinical trials. [70][71][72] Recently, Lappchen et al [73] synthesized close mimetics of calixarene 0118 of the types 8 and 9 (Scheme 4) and evaluated their cytotoxic properties. All the newly synthesized analogs were not only proved to be equipotent to calixarene 0118, but some of them also inhibited human umbilical vein endothelial cells (HUVEC) and MA148 ovarian carcinoma cell growth nearly 4-and 10-fold more effectively, which is a straightforward evidence of the potential of this class of compounds in anti-angiogenic…”
Section: Lower-rim-functionalized Calix[4] Arenesmentioning
confidence: 99%